Pycnogenol® Supplementation Prevents Recurrent Urinary Tract Infections/Inflammation and Interstitial Cystitis. (24th June 2021) - Ledda, A.; Hu, S.; Cesarone, M. R.; Belcaro, G.; Dugall, M.; Feragalli, B.; Cotellese, R.; Hosoi, M.; Ippolito, E.; Corsi, M.; Luzzi, R.
Abstract : This open pilot registry study aimed to evaluate and compare the prophylactic effects of Pycnogenol® or cranberry extract in subjects with previous, recurrent urinary tract infections (UTI) or interstitial cystitis (IC). Methods . Inclusion criteria were recurrent UTI or IC. One subject group was supplemented with 150 mg/day Pycnogenol®, another with 400 mg/day cranberry extract, and a group served as a control in a 2-month open follow-up. Results . 64 subjects with recurrent UTI/IC completed the study. The 3 groups of subjects were comparable at baseline. All subjects had significant symptoms (minor pain, stranguria, repeated need for urination, and lower, anterior abdominal pain) at inclusion. In the course of the study, the subjects reported no tolerability problems or side effects. The incidence of UTI symptoms, in comparison with the period before inclusion in the standard management (SM) group, decreased significantly; there was a more pronounced decrease in the rate of recurrent infections in the Pycnogenol® group (p < 0.05 ). The improvement in patients supplemented with Pycnogenol® was significantly superior to the effects of cranberry. At the end of the study, all subjects in the Pycnogenol® group were infection-free (p < 0.05 vs. cranberry). Significantly, more subjects were completely symptom-free after 2 months of management with Pycnogenol® (20/22) than with SM (18/22) and cranberry (16/20). Conclusions . This pilot registry suggests that 60 days of Pycnogenol® supplementation possibly decrease the occurrence of UTIs and IC without side effects and with an efficacy superior to cranberry.